Log traceability and supply-chain verification by DNA markers in Fagus sylvatica L. in Italy - Angela Teani; Giovanbattista de Dato (Annals of Silvicultural Research)
Verifying the match of a timber log with its population of origin represents a meaningful improvement for the preservation and valorisation of the wood chain.